2002
DOI: 10.1080/02786820290092087
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Mass-Weighted Size Distribution Measurements with the Model 3320 Aerodynamic Particle Sizer

Abstract: The ability of the Model 3320 aerodynamic particle sizer (APS) to make accurate mass-weighted size distribution measurements was investigated. Signi cant errors were observed in APS size distribution measurements with measured mass median aerodynamic diameters (MMADs) as much as 17 times higher than from cascade impactor measurements. Analysis of APS correlated timeof-ight and light scattering data indicated that the MMAD distortions were due to a few anomalous large particle measurements (» 0.1% of the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 12 publications
0
26
1
Order By: Relevance
“…4). In fact APS model 3320 is not capable of reliably measuring aerosol concentration above 10 µm due to recirculation of particles inside instrument (Stein et al, 2002). The used instruments, altogether, measured sizes from 0.4 nm to 20 000 nm.…”
Section: Trace Gas and Aerosol Concentrationsmentioning
confidence: 99%
“…4). In fact APS model 3320 is not capable of reliably measuring aerosol concentration above 10 µm due to recirculation of particles inside instrument (Stein et al, 2002). The used instruments, altogether, measured sizes from 0.4 nm to 20 000 nm.…”
Section: Trace Gas and Aerosol Concentrationsmentioning
confidence: 99%
“…However, the accuracy in calculating mass distribution was still limited by a very low-level background of false, large-particle counts revealed when the effect of the coincidence and phantom particles was eliminated. This analysis was in depth carried out by Stein et al (2002) with a CFD simulation of the particle patterns in the measurement domain of the APS. They found out small particles recirculated and reentered in the measurement domain with a considerable lower velocity, which makes them large from an aerodynamics point of view even if small optically.…”
mentioning
confidence: 99%
“…The underlying causes of bias due to high particle concentrations are different between the Aerosizer ® [109] and both earlier [95,96] and later [98] APS ® systems, on account of the different transit time detection methodologies. The Aerosizer ® can be used with the AeroDiluter ® to mitigate the problem, however a systematic study with a range of different pMDIgenerated aerosols found that significant particle coincidence occurred with some formulations with the maximum aerosol dilution that was available [108].…”
Section: ҁ1mentioning
confidence: 99%
“…Relative light scattering intensity can also be measured and correlated with the TOF-based aerodynamic size for each particle. Despite these improvements, accuracy in calculating mass-weighted size distributions most appropriate for medical inhaler assessments using the model 3320 was still limited by a very lowlevel background of false, large particle counts that were present even after the effects of particle coincidence and phantom particles had been eliminated [98,99]. The cause was traced to small particles that re-circulated in the vicinity of the measurement zone, thereby re-entering at a much slower velocity and therefore being assigned a correspondingly larger size.…”
Section: Time-of-flight Aerodynamic Particle Size Analyzersmentioning
confidence: 99%